If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12s + -24 = 0 Reorder the terms: -24 + 12s = 0 Solving -24 + 12s = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 12s = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 12s = 0 + 24 12s = 0 + 24 Combine like terms: 0 + 24 = 24 12s = 24 Divide each side by '12'. s = 2 Simplifying s = 2
| 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r | | v=25(30) | | -2x+17=8+x | | -12r-48=12 | | -(5-3x)-6(2x-4)=x+1 | | 24x^4=36x^3-12x^2/12x^2 | | 19+3c=40 | | 7log(4x-1)=14 | | 5b-5.25b+3=3.75 | | -4c+5=9 | | -12x^2/12x^2 | | 3y+6=6-5x | | -6n-8=10 | | 7ln(4x-1)=14 |